Calculation, Deposit, Reporting and Recording of VAT Accounting With E-Invoice On PT. Cipta Medika Indonesia - Gunawan, Enggun; Pramesti, Regita Adhia (International Publisher (YAPENBI), 2023)
VAT is a single tax that will be imposed on all transactions, both sales and purchases of goods and services that take place in Indonesia at a single rate as of April 2022, which is 11%. VAT is charged to individual taxpayers or business entities that obtain the status of a Taxable Entrepreneur (PKP). VAT and PPnBm have the same legal basis, namely Law Number 42 of 2009, which has been replaced or revoked by Law Number 7 of 2021 concerning Harmonization of Taxes. The purpose of this study is to find out how to calculate, deposit, report and record VAT with e-Faktur at PT Cipta Medika Indonesia. The data collection technique used is by using observation and interview methods. The data taken is real based on what is in the company. The results of this study indicate that calculating, depositing, reporting and accounting records VAT through the e-Faktur applications are very helpful and facilitate the process from accounting records to reporting at PT Cipta Medika Indonesia.